Preventive Measures for Peatland Forest Fires in Kumpeh Subdistrict, Muaro Jambi Regency - Edison; Siata, Ratnawaty; Nurchaini, Dewi Sri (Jurnal Karya Abdi Masyarakat, 2023)
Forest and peatland fires remain a significant threat in Kumpeh Subdistrict, Muaro Jambi Regency. This community engagement program aimed to enhance local capacity in fire prevention through training and assistance in the use of appropriate technology. The program was implemented in four stages: education, field visits, hands-on practice, and field consultation, targeting communities in Seponjen and Tanjung villages. The introduced technology integrated environmentally friendly and user-safe management approaches. Results indicated an improvement in community knowledge and skills in land management and fire prevention techniques. Moreover, residents began developing community forests as a sustainable source of income. The program also facilitated the dissemination of scientific knowledge and opened opportunities for forest-based livelihoods. A total of 80 participants were actively involved, and the activity significantly increased public awareness and participation in protecting the environment from fire hazards.